Analisis Preferensi Konsumen di Dua Coffee Shop Cabang Bintaro, Tangerang Selatan - PURBA, DOMENICO WEMILO; AMBARAWATI, I GUSTI AGUNG AYU; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2024)
Consumer Preferences Analysis in Dua Coffee Shop Bintaro Branch, South Tangerang.  The consumption of food and drink outside their homes has become a way of life for the Indonesian people. Coffee shop is a type of restaurant that people choose to consume food and drinks outside their homes. The increasing number of coffee shops leads to many alternative consumer choices as well as tight competition in the business. Tight competition and many alternative choices encourage coffee shops to adjust to consumer preferences in order to attract more consumers. This study aims to analyze consumer preferences at Dua coffee shop, Bintaro branch through a combination of coffee shop’s attributes that consumers like the most. Attributes to be examined include; attributes of coffee taste, price, location, facilities, and style of service. Data were obtained from interviews and processed using descriptive analysis and conjoint analysis with Statistical Package for the Social Science software. The results showed that the location attribute was considered the most important with an attribute importance value of 35,978. While the combination of attribute levels that consumers like the most is the sweet taste of coffee, the price range is from Rp.22,000 – Rp.33,500, located close to the main road, has large parking area, and has the style of plate service.